BEST PRACTICES FOR VIRTUAL EVENTS DURING THE COVID-19 PANDEMIC - FOCUSING ON ATTENDEE ENGAGEMENT - Ton, Han Nu Ngoc; Le, Ngoc Kim (Advances in Social Sciences Research Journal, 2021)
The COVID-19 pandemic constitutes a severe hazard: not only to human health but also to the economy on both a national and a global level. The pandemic has particularly affected the event industry, which relies on mass gatherings. This research aims to analyse the impact of COVID-19 on the event industry and propose best practices for virtual events in terms of attendee engagement. A qualitative research approach was applied to generate insights from industry experts in real contexts in Vietnam. The study drew on interviewees with four participants engaged in virtual events: two from the event industry, and two from the education sector. This research focuses on three key elements to enhance the level of attendee engagement in virtual events: the four realms of experience, storytelling and attendee objectives when joining a given event. The study also highlights the relationships among these three critical elements while offering theoretical contributions and suggesting best practices.